Comportamento de percolação em barragens de enrocamento com núcleo em concreto asfáltico - Rodrigo Melo (2012)
World economic growth leads to an increase in demand for water, whatever the purpose, also increasing the need for construction of dams for storage and / or adjustment of flow rates. The concern with the environment implies sometimes difficult to select local or availability of materials, making it necessary to search for alternative solutions. In thisdissertation the object of study of rockhll dams with asphalt concrete core (ACC). Analyzes were conducted on a section percolation hypothetical varying the hydraulic load and the thickness of the core, to evaluate the influence of the flow behavior of a dam. The analyzes given input for setting equations to predict flow through the core in a concrete asphalt ACC. These data can be useful for pre-sizing of a particular project and benchmarking with other solutions.